Scabies with Predilection Athypical in Elderly Patients : A Case Report - Zulfan Zulfan; Nanda Earlia; Fitria Fitria; Wahyu Lestari; Sri Rezeki Zakaria (Journal of Innovative and Creativity, 2025)
Scabies is an infectious skin disease caused by Sarcoptes scabiei infestation that is often found in vulnerable populations such as the elderly. In the elderly, clinical manifestations are often atypical and do not follow classic predilection patterns, which can cause delays in diagnosis and therapy. A 69-year-old woman presented with chronic itching of the perianal area since the last two months accompanied by skin thickening and rough surface. Physical examination showed papules confluent into erythematous plaques with lichenification in the perianal region. KOH skin scraping examination confirmed the presence of Sarcoptes scabiei mites. The patient was diagnosed with scabies with chronic lichen simplex due to repeated scratching. Therapy was given in the form of 5% permethrin cream, oral antihistamines (cetirizine), and topical corticosteroids to reduce inflammation, along with hygiene education and simultaneous treatment of family members. Scabies in the elderly may show atypical predilections, including the buttocks, face, or scalp areas. Decreased cellular immunity, physiological skin changes and comorbid factors influence susceptibility and clinical manifestations. Late diagnosis risks increasing the parasite burden and triggering complications. This case emphasizes the importance of clinical vigilance against atypical manifestations of scabies in the elderly. Early diagnosis, laboratory confirmation, and comprehensive management including patient and family education play an important role in preventing complications and recurrences